Air Management in Chemistry Laboratories to Prevent Sick Building Syndrome (SBS): A Mixed-Method Approach - Abdurrasyid; Helmi Geisfarad; Rian Adi Pamungkas; Aprilita Rina Yanti; Duan Elnastio; Diman Wahyudin (Postgraduate, University of Mataram, 2025)
Chemistry laboratories are inherently high-risk environments where poor Indoor Environmental Quality (IEQ) can contribute to Sick Building Syndrome (SBS)—a condition marked by symptoms such as headaches, respiratory irritation, and reduced concentration, which negatively affect user productivity and well-being. Ensuring optimal air circulation is critical to maintaining thermal comfort, air quality, and compliance with occupational health and safety standards. This study adopts a mixed-method approach using a sequential exploratory design to investigate user comfort perceptions in chemistry laboratories. Data were collected through surveys of 50 respondents from five educational institutions to capture the Voice of Customer (VoC) regarding environmental comfort. Qualitative findings were enriched through benchmarking and further analyzed using the House of Quality (HoQ) method to identify air circulation deficiencies and prioritize improvements. The analysis revealed that educational laboratories underperform in temperature control, humidity regulation, and air freshness when compared to industrial and training laboratories. Key factors affecting comfort include air circulation pathways (score = 42) and air regulation mechanisms (score = 36), followed by circulation points (score = 21) and air conditioning systems (score = 11). The proposed solution involves integrating cassette-type air conditioners with a Louver Fresh Air (LFA) system to enhance thermal stability and ensure fresh air exchange. These improvements are vital for preventing SBS, enhancing user well-being, and supporting effective laboratory-based learning.